The Influence Of Work Discipline And Work Environment On Employee Work Morale At The Tanjung Agung Sub-District Office, Muara Enim Regency - Kalpin Kalpin; Marko Ilpiyanto; Titi Hasanah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine the effect of work discipline and the work environment, individually and collectively, on employee morale at the Tanjung Agung Sub-district Office, Muara Enim Regency. This is a quantitative study using statistical calculations using multiple linear regression, partial tests (t-test), simultaneous tests (f-test), and coefficients of determination. The results showed that work discipline and the work environment significantly influence employee morale individually at the Tanjung Agung Sub-district Office, Muara Enim Regency. Work discipline and the work environment significantly influence employee morale simultaneously at the Tanjung Agung Sub-district Office, Muara Enim Regency.